Analysis of the frequency of pathologies of the cervical spine in adolescents according to computed tomography - Adamovych, O.; Yashchenko, A. (Journal of Education, Health and Sport, 2021)
Spinal pathologies today occupy a leading position in the rankings of diseases with a high degree of disability of patients, translating the problem into the category of medical and social. Cervical lesions are one of the most common manifestations of spinal pathology, and cervical osteochondrosis ranks second after lumbar. Literature sources indicate that today spinal pathologies have a pronounced tendency to rejuvenate. The aim of our study was to determine the frequency of pathological lesions of the cervical spine among adolescents in a randomized sample according to computed tomography. 100 series of anonymized computed tomograms of young people (18-21 years old) were processed. The examination was performed on the TSX-101A Aquilion 16. According to the analysis, only 22% of the examined young people do not have pathological changes in the study area. Changes in intervertebral discs in the form of protrusions of different localization were found in 51% of the examined persons, in 23% - intervertebral hernias. The high frequency of pathological lesions of the cervical spine indicates the need to identify the causes of their occurrence, as well as the development and application of effective preventive measures.